ANALISIS DAMPAK FASILITAS KERJA, SUPERVISI DAN MOTIVASI PADA KINERJA KARYAWAN PT. SARANA YOGYA VENTURA - Asteria, Beta; Muchsin, Alwan (STIE Wiyatamandala, 2023)
ABSTRACT This study used the associative method to analyze the influence of independent variables on the dependent variable, namely facilities (X1), supervision (X2), motivation (X3) on employee performance (Y). This research was conducted at PT. Sarana Yogya Ventura (SYV) which is located at Jalan Yos Sudarso No 25, Kota Baru, Gondokusuman, Yogyakarta. In this study, analysis was carried out with regression. Partially based on the t test, the results show that work facilities have a positive and significant effect on the performance of employees of PT. Sarana Yogya Ventura. This is evidenced by the value of t count 3.895 > t table 1.681. Partially, supervision has a positive and significant effect on the performance of employees of PT. Yogya Ventura facility. This is evidenced by the value of t count 1961 > t table 1681. Partially, work motivation has a positive and significant effect on the performance of employees of PT. Sarana Yogya Ventura. This is evidenced by the value of t count 2,844 > t table 1,681. Simultaneously work facilities, supervision, and motivation simultaneously affect the performance of employees of PT. Sarana Yogya Ventura. The test results show the calculated F value of 10,855 > F table of 2,839.